Infant Psychosocial Environment Predicts Adolescent Cardiometabolic Risk: A Prospective Study - Doom, Jenalee R. (J Pediatr, 2019)
OBJECTIVE: To prospectively assess whether the infant psychosocial environment was associated with cardiometabolic risk as early as adolescence. STUDY DESIGN: Participants were recruited in Santiago, Chile, and have been followed from infancy. Inclusion criteria included healthy infants with birth weight ≥3kg and a stable caregiver. The psychosocial environment, including depressive symptoms, stressful life events, poor support for child development, father absence, and socioeconomic status, was reported by mothers at 6–12 months. BMI z-score was assessed at 5 and 10 years. BMI z-score, waist-to-hip ratio, systolic and diastolic blood pressure, fat mass and body fat percentage, fasting glucose, total and HDL cholesterol, and homeostatic model of insulin resistance were tested in adolescence. RESULTS: Adolescents ranged from 16–18y (N = 588; 48.1% female). A poorer infant psychosocial environment was associated with BMI z-score at 10 years (β = 0.10, 95% CI = 0.00–0.19) and in adolescence (β = 0.15, 95% CI = 0.06–0.24) but not at 5 years. A poorer infant psychosocial environment was associated with higher blood pressure (β = 0.15, 95% CI = 0.05–0.24), greater anthropometric risk (β = 0.13, 95% CI = 0.03–0.22), greater biomarker (triglycerides, HOMA-IR, total cholesterol) risk (β = 0.12, 95% CI = 0.02–0.22), and a higher likelihood of metabolic syndrome in adolescence (aOR = 1.50; 95% CI = 1.06–2.12). CONCLUSIONS: These findings demonstrate that a poorer infant psychosocial environment was associated with greater adolescent cardiometabolic risk. The results support screening for infants’ psychosocial environments and further research into causality, mechanisms, prevention, and intervention.